2015
DOI: 10.1007/s40333-015-0127-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sand and dust storm source areas in Iran

Abstract: Sand and dust storms (SDS) are common phenomena in arid and semi-arid areas. In recent years, SDS frequencies and intensities have increased significantly in Iran. A research on SDS sources is important for understanding the mechanisms of dust generation and assessing its socio-economic and environmental impacts. In this paper, we developed a new approach to identify SDS source areas in Iran using a combination of nine related datasets, namely drought events, temperature, precipitation, location of sandy soils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(29 citation statements)
references
References 33 publications
3
26
0
Order By: Relevance
“…The persistence of this specific area of intense dust activity is suggesting that locations in this area are especially appropriate for dust generation. The results of mean monthly AI distribution for the last 11 years are confirmed in who identified Sand and Dust Storms source regions in Iran (see Figures and in ) showing that, regions which are located in South‐ West of Iran are possible local sand and dust storm origins . Comparing the mean monthly AI distribution with top soil layer wetness and surface skin temperature in the warm and cold periods for all 11 years shows a good agreement.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The persistence of this specific area of intense dust activity is suggesting that locations in this area are especially appropriate for dust generation. The results of mean monthly AI distribution for the last 11 years are confirmed in who identified Sand and Dust Storms source regions in Iran (see Figures and in ) showing that, regions which are located in South‐ West of Iran are possible local sand and dust storm origins . Comparing the mean monthly AI distribution with top soil layer wetness and surface skin temperature in the warm and cold periods for all 11 years shows a good agreement.…”
Section: Resultssupporting
confidence: 68%
“…Also, the surface skin temperature experienced a considerable increase during warm period especially in July which led to a notable reduction of top soil layer moisture. It can be seen in Figures 4 and 5 1 and 3 in [35]) showing that, regions which are located in South-West of Iran are possible local sand and dust storm origins [24]. Comparing the mean monthly AI distribution with top soil layer wetness and surface skin temperature in the warm and cold periods for all 11 years shows a good agreement.…”
Section: Meteorological Simulationsmentioning
confidence: 62%
“…A more precise look through the long‐term mean annual and monthly values and also the time series of CC shows that a great proportion of ASR S at the station Ahvaz originates from CSR S which may vary as a result of increase/decrease in the amount of aerosols. Recent studies with respect to aerosols show that dust and sand storms are frequent in the southwest of Iran (Cao et al, ; Sarraf et al, ; Middleton, ) and the highest amounts of aerosols is mostly observed during summer (Maleki et al, ). This is mainly caused by sand and dust storms blowing from eastern Syria and Iraq (Shahsavani et al, ; Amanollahi et al, ), in addition to the dust activities originating from severe soil degradation in the Hoor‐Al‐Howizeh/Al‐Azim marshes, which is mainly located in the Khuzestan province, in the southwest of Iran (Cao et al, ) and has dried up as a consequence of several factors such as droughts, climate change, dam construction projects, etc.…”
Section: Discussionmentioning
confidence: 99%
“…where c ′ is the normalized time series parameter and c min and c max are the minimum and maximum values in the series, respectively [38]. Some large-scale dynamics influence the tropospheric O 3 such as the quasibiennial oscillation (QBO) and the El Niño-Southern Oscillation (ENSO) related to the dynamical processes leading to a modulation of the stratospheric circulation and of the stratospheric-tropospheric exchanges (STE).…”
Section: Dynamical Variables and Regression Modelmentioning
confidence: 99%